InfoUSA information USA - United States. Department of State. Office of International Information Programs (Washington, D.C. Produced by the U.S. Dept. of State, 2000)
Authoritative resource for foreign audiences seeking information about U.S. policies, American society, culture and political processes.
Netscape Navigator 4.0 included.
Produced by the U.S. Department of State, April 2000.
System requirements: Web browser (Netscape 4.0, Internet Explorer, etc.); PDF reader (Adobe Acrobat).
Keywords: Law -- United States; Mass media -- United States; Information technology -- United States; Education -- United States